PERSEPSI NELAYAN SUKU LAUT TERHADAP PENDIDIKAN UNTUK MASA DEPAN ANAK DI DESA KUALA PATAH PARANG KECAMATAN SUNGAI BATANG KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - Syahputra, Syapril; Ramli, Mohammad (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThe research was conducted in June 2014 in Kuala Patah Parang Villageof Indragiri Hilir of Riau Province. The study him was to find out theperceptions and the chateristics correlation of fishermen âSuku Lautâ on futureeducation for the children. The research method used was a survey method. Thepopulation consisted of fishermen Suku Laut under 57 years old and the numberof head of house hold who activy in fishing. was 150 people and 40 people.Were taken as sample based on the results it showed that the perceptionsof fishermen Suku Laut on the education for the childrens futuren is growingbetter and the characteristics of Suku Laut including age, income, number offamily members and work experiences have no real correlations (non-significant)Keywords: Education, Perceptions and Characteristics of Suku Laut